Blood pressure in the acute period of ischemic stroke - E. A. Shirokov (Лечащий Врач)
Ischemic stroke is one of the leading causes of death and permanent disability. The mortality rate in the acute period of ischemic stroke remains high – from 8% to 20%, depending on the severity of acute cerebral circulatory disorders. Monitoring blood pressure in the acute period of stroke is an important tool for improving the outcomes of the disease. The author of the article questions the expediency of maintaining high blood pressure values in the acute period of ischemic stroke. New perfusion methods of brain research do not support the established ideas about the usefulness of high blood pressure in the first hours and days of ischemic stroke. The article discusses the mechanisms of violations of intracerebral hemodynamics and the influence of blood pressure on them. At least three mechanisms of the negative impact of severe arterial hypertension (AH) on the clinical situation in the acute period of stroke can be distinguished. First and foremost: high blood pressure (BP) does not at least improve cerebral perfusion, but at the very least worsens it not only in the area of damage, but also in areas of the brain remote from the site of ischemia. Second: excessive blood pressure increases the likelihood of hemorrhagic transformation of the ischemic focus and all variants of intracranial hemorrhage. Third: AH increases the load on the myocardium, which leads to a decrease in the minute volume of blood and, ultimately, a decrease in the volumetric rate of cerebral blood flow. The author gives his well-founded opinion on the optimal parameters of blood pressure in patients with ischemic stroke.